(untitled) (Iranian Journal of Kidney Diseases, 2020)
Introduction. Membranous glomerulonephritis (MGN) is the most common cause of nephrotic syndrome in adults. The gold standard techniques for diagnosis of MGN are based on a constellation of findings given by light microscope, electron microscope (EM), and immunofluorescence (IF). Occasionally, only formalin-fixed tissues are available for the analysis by light microscopy, which have limitations in differentiating minimal change diseases from MGN. Recently, the usage of C4d immunohistochemistry (IHC) has been proposed for the diagnosis of MGN. The aim of this study was to evaluate the accuracy of C4d-IHC in diagnosis of MGN. Methods. The present investigation conducted on patients with nephrotic syndrome who underwent renal biopsy in Labbafinejad hospital, from 2016 to 2017. The entire specimens were examined by light microscope, immunofluorescence, and electron microscope as a gold standard method for diagnosis of MGN. The samples were then stained for C4d immunohistochemical analysis. Eventually, the sensitivity, specificity, positive, and negative predictive value for C4d-IHC was determined. Results. The sensitivity and specificity of the C4d-IHC in order to differentiate MGN from other glomerulopathies were 95% and 87.5%, respectively. In addition, the negative and positive predictive values were 97.2% and 79.16%, respectively. Conclusion. It was ultimately attained that C4d-IHC has more accuracy in identification and diagnosis of MGN, in contrary to EM and IF, this method is more usable and cost effective, which requires a lower level of skill and advanced equipment. Indeed, this technique does not require fresh specimen.